The 'temporal effect' in hominids: Reinvestigating the nature of support for a chimp-human clade in bone morphology. Issue 88 (November 2015) - Pearson, Alannah; Groves, Colin; Cardini, Andrea
Abstract: In 2004, an analysis by Lockwood and colleagues of hard-tissue morphology, using geometric morphometrics on the temporal bone, succeeded in recovering the correct phylogeny of living hominids without resorting to potentially problematic methods for transforming continuous shape variables into meristic characters. That work has increased hope that by using modern analytical methods and phylogenetically informative anatomical data we might one day be able to accurately infer the relationships of hominins, including the closest extinct relatives of modern humans. In the present study, using 3D virtually generated models of the hominid temporal bone and a larger suite of geometric morphometric and comparative techniques, we have re-examined the evidence for a Pan-Homo clade. Despite differences in samples, as well as the type of raw data, the effect of measurement error (and especially landmark digitization by a different operator), but also a broader perspective brought in by our diverse set of approaches, our reanalysis largely supports Lockwood and colleagues' original results. However, by focusing not only mainly on shape (as in the original 2004 analysis) but also on size and 'size-corrected' (non-allometric) shape, we demonstrate that the strong phylogenetic signal in the temporal bone is largely related to similarities in size. Thus, with this study, we are not suggesting the use of a single 'character', such as size, for phylogenetic inference, but we do challenge the common view that shape, with its highly complex and multivariate nature, is necessarily more phylogenetically informative than size and that actually size and size-related shape variation (i.e., allometry) confound phylogenetic inference based on morphology. This perspective may in fact be less generalizable than often believed. Thus, while we confirm the original findings by Lockwood et al., we provide a deep reinterpretation of their nature and potential implications for hominid phylogenetics and we show how crucial it is not to overlook size in geometric morphometric analyses.